2008
DOI: 10.1530/eje-08-0413
|View full text |Cite
|
Sign up to set email alerts
|

Long-term GH treatment improves adult height in children with Noonan syndrome with and without mutations in protein tyrosine phosphatase, non-receptor-type 11

Abstract: Context: Noonan syndrome (NS) is characterized by short stature, typical facial dysmorphology and congenital heart defects. Short-term effect of GH therapy in NS is beneficial, reports on the effect on adult height are scarce. Objective: To determine the effect of long-term GH therapy in children with NS. Design: Twenty-nine children with NS were treated with GH until final height was reached. Setting: Hospital endocrinology departments. Patients: Children with the clinical diagnosis of NS, with mean age at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
120
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(127 citation statements)
references
References 23 publications
3
120
1
3
Order By: Relevance
“…Thus Kirk et al, observed a moderate increase in height SDS of 0.8 in 10 patients [22], which is in accordance with a rise of 0.87 in 24 patients reported by Raaijmakers et al, [29]. On the other hand, Osio et al, Noordam et al, and Romano et al, reported better outcomes of GH therapy, with increases in height SDS ranging from 1.3 to 1.7 on a total of 112 patients [26,28,30].…”
Section: Gh Therapy In Nssupporting
confidence: 65%
See 4 more Smart Citations
“…Thus Kirk et al, observed a moderate increase in height SDS of 0.8 in 10 patients [22], which is in accordance with a rise of 0.87 in 24 patients reported by Raaijmakers et al, [29]. On the other hand, Osio et al, Noordam et al, and Romano et al, reported better outcomes of GH therapy, with increases in height SDS ranging from 1.3 to 1.7 on a total of 112 patients [26,28,30].…”
Section: Gh Therapy In Nssupporting
confidence: 65%
“…In agreement with this, individuals mutated in PTPN11 appeared to respond less to GH therapy than other NS patients [25,27]. Supporting the concept of GH resistance in patients with PTPN11 mutations, other clinicians subsequently reported that these individuals display, under GH therapy, smaller increments in IGF-1 levels or in short-term growth, compared with subjects without PTPN11 mutations [28,53]. However, in one of these studies which also measured patients growth, long-term GH treatment was not found to make a significant difference on the growth of children harboring PTPN11 mutations, in comparison with other NS patients [28].…”
Section: Signs Of Gh Resistancementioning
confidence: 52%
See 3 more Smart Citations